Penerapan therapy gestalt dalam mengatasi trauma pada korban child trafficking - Era Annisa Emansi Saliha (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
Trafficking is the trade of humans, most commonly for the purpose of forced labor, sexual slavery, or commercial sexual exploitation for the trafficker or others. This paper is focus on the child trafficking which is one of the major problems in Indonesia and how to resolve their trauma with gestalt therapy. Trauma on child trafficking caused by violence, abuse and space restrictions. Findings that trafficking gave risks to the physical, psychological, spiritual, and sosial-emotional of young victims. Assistance is needed to assist victims of child trafficking in order to restore the original psychological condition. The most important thing in dealing with trauma on child trafficking is to build trust and give them a sense of security. Gestalt therapy techniques are useful to help victims of child trafficking gain full of awarness here and now.